Institutional capacity to dynamically innovate. An application to the Portuguese case - Vicente Galindo, Purificación (2014)
The present paper addresses the dynamics of innovation, by extending the analysis beyond a static-economic perspective. It offers a dynamic-institutional mapping of relational capacities to dynamically innovate. Its main goal is to contribute to the above-mentioned research theme by presenting a new methodology able to pinpoint different trends in the relational capacities of institutions when they are innovative. Thereby, major characteristics in the networks of innovation are identified. This investigation uses an extended set of private institutions and public organizations located in Portugal, evaluated by their WebPage contents. To this data set a new combination ofmultivariate statistical methods is applied to detect group performances, to compare them, and to identify gradients of capacity to dynamically innovate. The results demonstrate that this method can provide extremely useful and tailor-made information for policy evaluation at regional or national levels.